PETROGENESIS OF PASIR CUPU DIORITE, PLERED DISTRICT, PURWAKARTA, WEST JAVA - Fachrudin, Kurnia Arfiansyah; Aini, Hana Nur; Syafri, Ildrem; Luthfi, Ahmad; Amitama, Emilia Bunga (Journal of Geological Sciences and Applied Geology, 2018)
Pasir Cupu located in the area of Plered and Sukatani, Purwakarta, West Java. It is geographically on 107o 26 '25.2' - 107o 27 '16.8' Easternmost and 6o 37 '22.8' - 6o 37 '03 "Southtermost. The Pasir Cupu is a formally formed intrusion, and classified into diorite (Streckeisen, 1978 in Gillespic and Styles, 1999). The method used is petroloogy, petrographic, and geochemical analysis using the XRF and CIPW methods. The megascopic appearance shows gray-colored rocks - in fresh, black-brown gray - in weathered ones; masive; very hard; fanheritic porphyritic textures; contains dark and bright minerals, dark minerals estimated to be amphibol, and pyroxene, and minerals that are bright feldspar; and masasaras are gray. Microscopic observations of 3 thin section of rock samples (CP 1, CP2 and CP3), showed porphyritic-afanitic texture, hypocrystalline, hypidiomorphic; composed of phenocryst plagioclase, amphibol, pyroxene, biotite, with mineral sizes between 0.1 mm - 4 mm; there are also small amounts of opaque, K-feldspar, quartz and carbonate minerals; with medium-coarse-grained bottom, consisting of plagioclase microlite, amphibole microlite, pyroxene and biotite microlite, carbonate minerals, chlorite and clay minerals. Based on geochemical analysis, Pasir Cupu is composed by diorite according to the Total Alkali Silica diagram. The magmatic series is included in the Calc-Alkaline and Thoeliitic series, the types of magma include the High-K and Medium-K (Calc-Alkaline Series) groups, as long as magma interacts with continental crust (continent), as long as the magma is based on the Island Arc Calc -Alkaline Basalt, the origin of magma origin ranged ± 140 Km - ± 185 Km in the Benioff zone and formed at temperatures of 1016 ̊ – 1062 ̊ C with rock specific gravity of 2.82 - 2.89 gram / cm3.